Metabolic reprogramming of glucose: the metabolic basis for the occurrence and development of hepatocellular carcinoma - Wang, Kai; Li, Xiaodan; Guo, Shuwei; Chen, Junsheng; Lv, Yandong; Guo, Zhiqiang; Liu, Hongzhou (Frontiers in Oncology, 2025)
Primary liver cancer is a common malignant tumor of the digestive system, with hepatocellular carcinoma (HCC) being the most prevalent type. It is characterized by high malignancy, insidious onset, and a lack of specific early diagnostic and therapeutic markers, posing a serious threat to human health. The occurrence and development of HCC are closely related to its metabolic processes. Similar to other malignant tumors, metabolic reprogramming occurs extensively in tumor cells, with glucose metabolism reprogramming being particularly prominent. This is characterized by abnormal activation of glycolysis and inhibition of oxidative phosphorylation and gluconeogenesis, among other changes. Glucose metabolism reprogramming provides intermediates and energy for HCC to meet its demands for rapid growth, proliferation, and metastasis. Additionally, various enzymes and signaling molecules involved in glucose metabolism reprogramming play irreplaceable roles. Therefore, regulating key metabolic enzymes and pathways in these processes is considered an important target for the diagnosis and treatment of HCC. This paper reviews the current status and progress of glucose metabolism reprogramming in HCC, aiming to provide new insights for the diagnosis, detection, and comprehensive treatment strategies of HCC involving combined glucose metabolism intervention in clinical settings.